2016
DOI: 10.2139/ssrn.2815996
|View full text |Cite
|
Sign up to set email alerts
|

Un-Diversifying During Crises: Is It a Good Idea?

Abstract: High levels of correlation among fi nancial assets, as well as extreme losses, are typical during crisis periods. In such situations, quantitative asset allocation models are often not robust enough to deal with estimation errors and lead to identifying underperforming investment strategies. It is an open question if in such periods, it would be better to hold diversifi ed portfolios, such as the equally weighted, rather than investing in few selected assets. In this paper, we show that alternative strategies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…This section studies the out-of-sample performance of the SLOPE procedure, considering a minimum variance framework, as typical of most studies (see i.e. Jagannathan and Ma (2003), Brodie et al (2009), DeMiguel et al (2009a, Giuzio and Paterlini (2016)).…”
Section: Set Up and Datamentioning
confidence: 99%
See 3 more Smart Citations
“…This section studies the out-of-sample performance of the SLOPE procedure, considering a minimum variance framework, as typical of most studies (see i.e. Jagannathan and Ma (2003), Brodie et al (2009), DeMiguel et al (2009a, Giuzio and Paterlini (2016)).…”
Section: Set Up and Datamentioning
confidence: 99%
“…After falling slightly, the correlation increases again in 2012, during the European sovereign debt crisis. The correlation coefficient plays an important role for our following analysis, as increased positive correlation among the constituents is reported to reduce the effects of diversification (Choueifaty and Coignard 2008, You and Daigler 2010, Giuzio and Paterlini 2016. For all portfolios, the optimal weights vector, ŵt , depends on the choice of the optimal λ parameter value.…”
Section: Sp500mentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, Fastrich et al (2015) showed that sparse portfolios derived from penalized regression models provide improvements in terms of a lower concentration and turnover. Giuzio and Paterlini (2018) highlighted the positive impact of regularized models on the portfolio performance during stressed market conditions. Kremer et al (2018) used regularization techniques to minimize the risk in multi-factor portfolios.…”
Section: Introductionmentioning
confidence: 98%